Aggregate public-private remuneration patterns in South Africa - Andreas Wörgötter; Sihle Nomdebevana (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2018)
This paper investigates the public-private remuneration pattern in South Africa since the introduction of an inflation-targeting framework in 2000. Co-integration tests and analysis confirm that there is a stable, long-run relationship between nominal and real remuneration in the public and private sector. The adjustment to the deviations from this long-run relationship is strong and significant for public-sector remuneration, while private-sector wages neither respond to the deviations from the long-run relationship nor lagged changes of public sector remuneration. The causal direction from private- to public-sector remuneration does not change if real earnings are calculated with the gross domestic product (GDP) deflator. This is confirmed by simple Granger causality tests. If this pattern remains stable, efforts to slow down the speed of the wage-price spiral should not exclude the private sector.
Keywords: 330